The Integration of Fair Trade Concepts and Maqashid Shari'ah as Criticism of the Free Trade Concept - Ramadhani, Jennifer Sakti; Az-zahra, Elsa Iqlima; Latief, Mohamad (Perhimpunan Intelektual Muslim Indonesia, 2025)
In the era of globalization, the concept of Free Trade has dominated international trade policies, emphasizing liberalization and minimal government intervention. However, there is growing criticism of the negative impacts of Free Trade on justice, the environment, and the economy. This research aims to analyze the integration between the Fair Trade concept and Sharia Economic principles as one of the concepts that can criticize the Free Trade concept. Fair Trade emphasizes fair trade by ensuring that producers in developing countries practice economic fairness. Likewise, the principles of Sharia Economics emphasize distributive justice, transparency, and sustainability. The integration of these two concepts can create a framework that promotes fair, sustainable trade oriented toward community welfare. Drawing on qualitative sources—journals, books, and previous research —this article explains how these two concepts can complement each other in the current global economic context. The results of this research show that integrating Fair Trade and Sharia Economics can provide fairer solutions to address global trade challenges, promote justice, and ensure economic prosperity for all parties involved. This article offers insights into the current international trading system and further explores the potential for cooperation between these two concepts. The integration of Fair Trade and Sharia Economics is not only a critique of the Free Trade concept but also an effort to build a trade system that is fairer, more sustainable, and oriented towards human values and justice.